Pengaruh Disparitas Pendidikan terhadap Kualitas Pendidikan di Kota Pelajar Yogyakarta: Studi Kasus Sekolah Islam Negeri Kota Sleman dan Gunung Kidul - Muhamad Reza Syahputra; Naufal Ahmad Rijalul Alam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of educational access and school infrastructure on the quality of education, as well as to identify the factors causing educational disparities between Sleman Regency and Gunungkidul Regency. The research method employed a quantitative approach using multiple linear regression analysis through t-tests and F-tests. The results indicate that educational access has a significant effect on the quality of education, with a t-value of 2.855 and a significance value of 0.017 (< 0.05). Conversely, school infrastructure does not have a significant partial effect on the quality of education, with a t-value of -0.007 and a significance value of 0.995 (> 0.05). However, simultaneously, educational access and school infrastructure have a significant effect on the quality of education, with an F-value of 4.544 and a significance value of 0.039 (< 0.05). Educational disparities between Sleman and Gunungkidul are influenced by differences in geographical accessibility, limited transportation facilities, unequal distribution of schools, socioeconomic conditions of the community, and the quality of educational resources. To reduce these disparities, several strategies are required, including improving educational access through the development of schools and transportation facilities, ensuring equitable distribution of schools and educators, improving infrastructure quality, utilizing educational technology, and providing educational assistance for underprivileged communities. The findings of this study emphasize that improving educational access is a key factor in enhancing educational quality and reducing educational disparities between regions.